2020
DOI: 10.1039/d0ra05900e
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid red blood cell membrane coated porous silicon nanoparticles functionalized with cancer antigen induce depletion of T cells

Abstract: We report a study on the effect of red blood cell membrane based cancer antigen-functionalized nanoparticles on peripheral blood T cells. These nanoparticles induce apoptosis of T cells and they may have use in treating autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…[31][32][33] An example of this is a hybrid NP functionalized with a model cancer antigen, tyrosinase-related protein-2, which was developed to induce the apoptotic cell death of T cells without altering the relative ratio of CD4 þ to CD8 þ T cells in autoimmune diseases. [34] In addition, nano-based strategies can be used to stimulate and maintain long-term immune tolerance in T cells that can restore immune regulatory networks. [35,36] For example, Zhang et al designed a mPEG-PLGA-PLL nanodelivery system to T A B L E 1 Antigen-specific immune tolerance methods.…”
Section: Current Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…[31][32][33] An example of this is a hybrid NP functionalized with a model cancer antigen, tyrosinase-related protein-2, which was developed to induce the apoptotic cell death of T cells without altering the relative ratio of CD4 þ to CD8 þ T cells in autoimmune diseases. [34] In addition, nano-based strategies can be used to stimulate and maintain long-term immune tolerance in T cells that can restore immune regulatory networks. [35,36] For example, Zhang et al designed a mPEG-PLGA-PLL nanodelivery system to T A B L E 1 Antigen-specific immune tolerance methods.…”
Section: Current Treatmentsmentioning
confidence: 99%
“…Biodegradable PLGA nanoparticles loaded with protein, peptide antigens, epitopes, or rapamycin [26][27][28] Immune system Antigen-specific immune tolerance induction in mice with encephalomyelitis, peanut allergy, or OVAinduced anaphylaxis [15][16][17][18] Promotion of differentiation of naïve T cells into antigen-specific Tregs [13,14,[26][27][28][29][30] Hybrid NP [10,35,36] T cells in autoimmune diseases Induce immune tolerance Hybrid NP functionalized with cancer antigen induces apoptotic cell death in pathogenic T cells without altering the CD4 þ and CD8 þ T cell ratio [16][17][18][19][20]25,[31][32][33][34][35] Nano-delivery transport system [14,37] Immune regulatory networks To simulate and maintain long-term immune tolerance regulatory T cells that can restore immune regulatory networks Transported a Treg-mediated stabilizer (miR-125a) into splenic T cells, thereby correcting the effector and regulatory T cell balance and improving the SLE disease progression transport miR-125a (a stabilizer of Treg-mediated selftolerance with specific effects) into splenic T cells to correct the imbalance of effector/Tregs and significantly inhibit systemic lupus erythematosus (SLE) disease progression. [37] Inorganic NPs, such as gold (Au) and mesoporous silicon (pSi), have been designed to target dendritic cells (DCs) to induce immune tolerance.…”
Section: Silences Sirna In Cells and Skin And Reduces T Cell Activity...mentioning
confidence: 99%
See 1 more Smart Citation
“…Red blood cell immunity mainly includes identifying and carrying antigen, eliminating circulating immune complexes, enhancing the immune response of T lymphocytes, and promoting the phagocytosis of immune complexes by macrophages. Red blood cells have peroxidase on the surface of their cell membranes, which plays the same killing effect on immune complexes as macrophages [ 5 ]. There are a large number of red blood cells; the number of red blood cells is more than 1,000 times the number of white blood cells.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that the as-prepared 155Tb loaded SiNPs could be used in targeted radionuclide therapy combined with a chemotherapeutic payload within the porous SiNPs. In another report, Santo's group 142 covalent attachment of a model cancer antigen TRP2, either expressed at the membrane surface or covered by membrane encapsulation, is promising for treating autoimmune diseases by inducing an autoantigen specific immune tolerance.…”
Section: Silicon-based Particles As Drug Delivery Carriersmentioning
confidence: 99%